The effect of fall-proof training on functional capacities, working memory and Muscle strength of the elderly with stroke - Farahnaz Ayatizadeh Tafti; Saeed Abedinzadeh Masuleh; Mohammad Reza Sadeghian Shahi; Hamidreza Maleki nezhad (فیزیولوژی ورزش و فعالیت بدنی)
Background and purpose: Despite the advances in modern medicine, drugs and medical technology, stroke diseases cause significant complications to people and always result in a decrease in performance, working memory and muscle strength. The aim of the present study was to investigate the effect of fall-proof training on functional capacities, working memory and Muscle strength of the elderly with stroke.Materials and Methods: 24 elderly patients suffering from a stroke were divided into two experimentally equal groups and control. The experimental group performed fall-proof exercises for eight weeks, and the control group did not perform any intervention. Training session consisted of 10 minutes of warm-up and stretching, 15 minutes of strength training, 25 minutes of multi-sensory system balance training, the center of gravity control, and posture strategies. In this study, to evaluate the functional capacity of the subjects, from three tests including: get up and go test, a 6-minute walking test, and 8-foot walking agility test, to evaluate working memory using the Wechsler working memory software and to evaluate muscle strength two tests of 30 seconds of lateral climbing and 30 seconds of sitting to standing were used.Results: Working memory (P = 0.002), stand up and go test (P < 0.001), 6-minute walk test (P = 0.020), 8-foot walk agility test (017 P = 0.01) and the 30 second lateral up test (P = 0.013) had a significant difference in the two experimental and control groups. Working memory (P = 0.001), stand up and go test (P < 0.001), 6-minute walk test (P = 0.009) and 8-feet walk agility test (P = 0.009), 30 seconds of sit-to-stand (P = 0.032) and 30-s Lateral Step Up Test (P = 0.013) in the experimental group increase significantly in the post-test stage compared to the pre-test. Also, the intra-group test did not show any significant difference in any of the variables in the control group in the post-test compared to the pre-test. Conclusion: The results showed that fall-proof exercises have led to an increase in working memory, functional index and muscle strength in the elderly with stroke. Due to the multi-dimensional effects of fall-proof exercises and the multifactorial nature of stroke, fall-proof exercises can be used in rehabilitation programs for the elderly with stroke.